2005
DOI: 10.1038/nature04223
|View full text |Cite
|
Sign up to set email alerts
|

BDNF from microglia causes the shift in neuronal anion gradient underlying neuropathic pain

Abstract: Neuropathic pain that occurs after peripheral nerve injury depends on the hyperexcitability of neurons in the dorsal horn of the spinal cord. Spinal microglia stimulated by ATP contribute to tactile allodynia, a highly debilitating symptom of pain induced by nerve injury. Signalling between microglia and neurons is therefore an essential link in neuropathic pain transmission, but how this signalling occurs is unknown. Here we show that ATP-stimulated microglia cause a depolarizing shift in the anion reversal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
1,566
7
17

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,732 publications
(1,687 citation statements)
references
References 28 publications
51
1,566
7
17
Order By: Relevance
“…Interestingly, intrathecal injection of ATP-activated microglia in the spinal cord is sufficient to induce pain (Tsuda et al, 2003). Further studies indicate that ATP-activated microglia can enhance pain by producing the growth factor BDNF (Coull et al, 2005). BDNF can act on lamina I neurons in the spinal cord to remove GABA inhibition by altering chloride reverse potential (Coull et al, 2005).…”
Section: The Role Of Microglia In Pain Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, intrathecal injection of ATP-activated microglia in the spinal cord is sufficient to induce pain (Tsuda et al, 2003). Further studies indicate that ATP-activated microglia can enhance pain by producing the growth factor BDNF (Coull et al, 2005). BDNF can act on lamina I neurons in the spinal cord to remove GABA inhibition by altering chloride reverse potential (Coull et al, 2005).…”
Section: The Role Of Microglia In Pain Controlmentioning
confidence: 99%
“…Further studies indicate that ATP-activated microglia can enhance pain by producing the growth factor BDNF (Coull et al, 2005). BDNF can act on lamina I neurons in the spinal cord to remove GABA inhibition by altering chloride reverse potential (Coull et al, 2005). ATP may also activate P2X7 receptors in spinal microglia to enhance pain (Donnelly-Roberts et al, 2007;Inoue, 2006).…”
Section: The Role Of Microglia In Pain Controlmentioning
confidence: 99%
“…Either blocking or deleting these receptors results in decreased neuropathic pain (Tsuda et al, 2003;Verge et al, 2004;Zhuang et al, 2006b). Intrathecal injection of ATP-activated microglia induces mechanical allodynia (a nociceptive response to normally innocuous mechanical stimulation) that requires microglial production of BDNF (Tsuda et al, 2003;Coull et al, 2005). A non-specific microglial inhibitor minocycline prevents/delays pain development (Raghavendra et al, 2003;Ledeboer et al, 2005;Hua et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The case for P2X 4 R remains tentative, largely due to the absence of selective P2X 4 R antagonists and the complicating presence of P2X 7 R, which is generally co-expressed with P2X 4 R in macrophages and microglia [3]. P2X 4 R does not appear to couple to any of the same downstream signalling cascades as has been demonstrated for P2X 7 R but studies with P2X 4 R gene-deleted mice have revealed abrogation of tactile allodynia in animal models of inflammatory (formalin-induced) and neuropathic (nerve section) pain via yet-to-be identified alterations in microglial functions [12][13][14].P2X 4 R expression at the plasma membrane of neurones and macrophages is subject to tight regulation by rapid recycling via the AP2/clathrin-dependent endocytic pathway [15,16]. Qureshi et al [17] have recently found that phagocytosis of zymosan or latex beads by mouse peritoneal macrophages lead to accumulation of P2X 4 R at the phagosome membrane; when lysosomal exocytosis was induced by the calcium ionophore, ionomycin, a significant increase in the plasma membrane surface expression of P2X 4 R occurred with concomitant increase in the ATP-evoked currents.…”
mentioning
confidence: 98%
“…The case for P2X 4 R remains tentative, largely due to the absence of selective P2X 4 R antagonists and the complicating presence of P2X 7 R, which is generally co-expressed with P2X 4 R in macrophages and microglia [3]. P2X 4 R does not appear to couple to any of the same downstream signalling cascades as has been demonstrated for P2X 7 R but studies with P2X 4 R gene-deleted mice have revealed abrogation of tactile allodynia in animal models of inflammatory (formalin-induced) and neuropathic (nerve section) pain via yet-to-be identified alterations in microglial functions [12][13][14].…”
mentioning
confidence: 98%